Factors Influencing Consumer Satisfaction Towards E-hailing Service Among Malaysian - Daphine Yeo Hooi Ann,; Muhammad Ammar Shafi, (Research in Management of Technology and Business, 2022)
E-hailing services are on-demand vehicles acquisition services that rely on Internet connectivity and the usage of a specialised digital application. Customers' need for online transportation has grown with the launch of e-hailing apps, due to the convenience it provides in recent times. The legalisation of ehailing services in Malaysia has accelerated the industry's expansion. However, ehailing does not have a fixed rate pricing during peak hour like others public transport, in which this has cause dissatisfaction of consumer for paying extra charges. As a result, the purpose of this study was to examine the most dominant factors influencing consumer use of e-hailing services in Malaysia, as well as to assess the relationship between factors influencing consumer satisfaction and e-hailing services in Malaysia. In this study, the quantitative method was applied. The questionnaires have been distributed to the respondents in Malacca, Malaysia, using Google Forms. The data was collected and analysed using the Statistical Package for Social Science (SPSS), with a response rate of 39.06 percent. The descriptive analysis revealed that perceived ease of use was one of the most important factors influencing the use of e-hailing services in Malacca. E-hailing service and perceived convenience showed a significant relationship. While there was no significant relationship between e-hailing and mobile payment, price, perceived ease of use, or perceived usefulness. The findings could be used as a reference for future e-hailing companies